The level aural comprehension of american english among EFL salvadoran learners - Deleón, Balmore; Mejía Méndez, Fredi Salvador; Quinteros Mejía, José Antonio (2024)
This research would benefit teachers as well as students in the way they see listening, and how they can take advantage of listening. Generally foreign language educators pay little attention to listening. Now is the time to do it because listening is really fundamental by the time we communicate. Knowing the strategies, and activities as well as the difficulties that students face in the listening, it is necessary to take into account what is developed in this essay. It can help to improve the listening performance for foreign language educators and learners through it. This essay can be taken as a referential framework since here are exposed the proper characteristics of the English language to put them into practice when teaching and learning English as well as the difficulties are explained here to overcome this issue. The most important contribution is that here is a bibliographical essay to be expanded by future learners.